Novel targets in renal fibrosis based on bioinformatic analysis - Yuan, Yuan; Xiong, Xi; Li, Lili; Luo, Pengcheng (Frontiers in Genetics, 2022)
Background: Renal fibrosis is a widely used pathological indicator of progressive chronic kidney disease (CKD), and renal fibrosis mediates most progressive renal diseases as a final pathway. Nevertheless, the key genes related to the host response are still unclear. In this study, the potential gene network, signaling pathways, and key genes under UUO model in mouse kidneys were investigated by integrating two transcriptional data profiles. Results: A total of 537 DEGs were shared by the two datasets. GO and the KEGG analysis showed that DEGs were typically enriched in seven pathways. Specifically, five hub genes (Bmp1, CD74, Fcer1g, Icam1, H2-Eb1) were identified by performing the 12 scoring methods in cytoHubba, and the receiver operating characteristic (ROC) curve indicated that the hub genes could be served as biomarkers. Conclusions: A gene network reflecting the transcriptome signature in CKD was established. The five hub genes identified in this study are potentially used for the treatment and/or diagnosis CKD as biomarkers.